Faktor-Faktor Yang Berpengaruh Terhadap Ketepatan Waktu Penyampaian Laporan Keuangan Perusahaan Tercatat di Bursa Efek Indonesia - Firjatullah, Muhammad Diky; Respati, Novita WeningTyas (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2023)
Timeliness of financial reporting is a structured presentation of the financial position and financial performance of an entity as well as the final results of accounting activities that show financial condition within a certain period of time. The purpose of this study is to examine and analyze the effect of institutional ownership, audit committee, independent commissioner, managerial ownership and audit quality on the timeliness of financial statement submission The population in this study is all companies listed on the Indonesia Stock Exchange in 2020. This research uses secondary data types through IDX web sites or through related company web sites. The number of data studied was 669 companies. The data analysis technique used is logistic regression analysis. The results of this study show that institutional ownership, audit committee, institutional ownership and audit quality have no effect on the timeliness of financial statement submission. Other findings show that independent commissioners have a positive influence on the timeliness of financial statement submission. The results of this study show that supervision from the independent board of commissioners is able to influence management in preparing timely financial statements.